(untitled) (Research, Society and Development, 2020)
The aim of this study was to evaluate the results of using a virtual application in the language therapy of a subject with non-fluent aphasia. Method: First, a virtual application based on the SVOX Brazilian Portuguese Luciana Voice system (text-voice) was created, installed on a mobile device, with Android 2.1 technology. The elaboration of this application took as a principle the sensorimotor continuity (acoustic-articulatory and visual-articulatory). The patient underwent conventional therapy for three months without the application and, later, another three months with the application. Results: In the first three months, there was an increase in more conventional gestures, favoring the subject’s communication and improving the interlocutor’s understanding. Nevertheless, the use of the application led to a considerable decrease in stereotypy, which caused great disruption in the subject’s oral production and made it impossible to understand his speech without the use of gestures and writing, concomitantly. Conclusion: the application was efficient as a therapeutic tool to improve the subject’s oral production by suppressing stereotypy.